Tinjauan Hukum Islam dan UU No 13 Tahun 2003 tentang Ketenagakerjaan terhadap Hak Upah Tenaga Honorer - Afrah Nur Athifah; Encep Abdul Rojak; Akhmad Yusup (UNISBA Press, 2023)
Abstract. According to Hanafiyah scholars, wages/ujrah are transactions for a benefit with certain permissible rewards. So, wages are a form of compensation for services that have been provided by workers. Wages according to Law No. 13 of 2003 concerning Manpower concerning the definition of wages in Article 1 paragraph 30 which reads: